2020
DOI: 10.2196/24225
|View full text |Cite
|
Sign up to set email alerts
|

An Easy-to-Use Machine Learning Model to Predict the Prognosis of Patients With COVID-19: Retrospective Cohort Study

Abstract: Background Prioritizing patients in need of intensive care is necessary to reduce the mortality rate during the COVID-19 pandemic. Although several scoring methods have been introduced, many require laboratory or radiographic findings that are not always easily available. Objective The purpose of this study was to develop a machine learning model that predicts the need for intensive care for patients with COVID-19 using easily obtainable characteristics… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 33 publications
(49 reference statements)
1
43
1
Order By: Relevance
“…As complexity in medical information has increased, there has been progressive interest in the application of machine learning to facilitate clinical decision-making. Such algorithms have been studied in a diverse array of applications, including sepsis prediction, 52 COVID-19 prognosis, 53 population health, 54 and cyberbullying. 55 In the present study, before the COVID-19 pandemic, 6 , 7 ensemble time-series forecasting models accurately predicted 70 of 72 monthly pediatric admission rates (97.2%) between July 2019 and December 2019.…”
Section: Discussionmentioning
confidence: 99%
“…As complexity in medical information has increased, there has been progressive interest in the application of machine learning to facilitate clinical decision-making. Such algorithms have been studied in a diverse array of applications, including sepsis prediction, 52 COVID-19 prognosis, 53 population health, 54 and cyberbullying. 55 In the present study, before the COVID-19 pandemic, 6 , 7 ensemble time-series forecasting models accurately predicted 70 of 72 monthly pediatric admission rates (97.2%) between July 2019 and December 2019.…”
Section: Discussionmentioning
confidence: 99%
“…of CPP* AI methods Predictors Val. methods Performance (AUC, Accuracy (Acc%), Sensitivity (SEN%), Specificity (SPE%), PPV/NPV (%), (95% CI)) Risk of Bias**: Participants/Predictors/Outcome/Analysis/Overall Muhammad et al [9] , South Korea, Recovery prediction, disease progression unclear DT, SVM, NB, LR, RF, K-NN unclear 5-FCV Acc 99.85 (Decision Tree) H U U U H Cheng et al [78] , United States, Severity Assessment, (risk prioritization tool that predicts ICU transfer within 24 h) 1987 RF respiratory failure, shock, inflammation, renal failure TTS, 10-FCV AUC 79.9 (95% CI: 75.2–84.6), Acc 76.2 (95% CI: 74.6–77.7), SEN 72.8 (95% CI: 63.2–81.1), SPE 76.3% (95% CI: 74.7–77.9) H H H H H Kim et al [79] , South Korea, ICU need prediction 4787 55 ML models developed, (XGBoost model revealed the highest discrimination perf.) age, sex, smoking history, body temperature, underlying comorbidities, activities of daily living (ADL), symptoms TTS AUC 0.897, (95% CI 0.877–0.917) H U H U H Yadaw et al [101] , United States, Mortality prediction 4802 ML, RF, LR, SVM, XGBoost age, minimum oxygen saturation over the course of their medical encounter, type of patient encounter (inpatient vs outpatient and telehealth visits) TTS AUC 91 L H H H H Klann et al [102] , USA, France, Italy, Germany, Singapore, Severity assessment 4227 ML PaCO2, PaO2, ARDS, sedatives, d-dimer, immature granulocytes, albumin, chlorhexidine, glycopyrrolate, palliative care encounter 5-FCV, TTS AUC 0.956 (95% CI: 0.952, 0.959) U U U H H Navlakha et al [103] , United States, Severity assessm...…”
Section: Resultsmentioning
confidence: 99%
“…In the participants domain, 30 studies had high risk of bias and 21 unclear. Sources of bias in the participants domain varied from small or incomplete datasets to exclusion criteria indicating the need of further data collection to test the generalizability of the developed AI models to other patient populations [2] , [7] , [15] , [16] , [17] , [35] , [37] , [43] , [48] , [57] , [59] , [65] , [69] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] . Thirty studies had high RoB in the “predictors” domain related to different ways of definitions and assessment for all participants or predictors availability.…”
Section: Resultsmentioning
confidence: 99%
“…These 8 variables have been reported as important predictor variables in the medical literature [23][24][25][26][27][28]. Specifically, age, shortness of breath, body temperature, lymphocytes, and hemoglobin have been reported as variables for predicting admission to the intensive care unit [23,25], critical illness [24,29], or severe disease [26,27,30]. In particular, Wu et al [26] reported that the severe group had a significantly lower platelet and higher WBC counts than the nonsevere group.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Our results indicate that age, body temperature, SOB, lymphopenia, a low hematocrit, low hemoglobin, a low platelet count, and a high WBC count were risk factors positively associated with the maximum clinical severity of COVID-19. These 8 variables have been reported as important predictor variables in the medical literature [23][24][25][26][27][28]. Specifically, age, shortness of breath, body temperature, lymphocytes, and hemoglobin have been reported as variables for predicting admission to the intensive care unit [23,25], critical illness [24,29], or severe disease [26,27,30].…”
Section: Principal Findingsmentioning
confidence: 99%